Hubungan Pola Asuh Orang Tua Terhadap Perkembangan Bahasa Anak Prasekolah (3-5 Tahun) Di PAUD Al-Hasanah Tahun 2014 - Joni Joni (LPPM Universitas Pahlawan Tuanku Tambusai, 2015)
The rate of child language development at age varies. Proficiency is influenced by internal factors and external factors. One environment that impact on children's language development is parenting parents. The purpose of this study was to determine the relationship between parenting parents on children's language development. The method used in the study was a descriptive cross sectional analititik. The population of this study were 30 children. In this study, samples were taken by total sampling. The study was conducted by distributing questionnaires and observation sheets. Research results obtained from the data parenting permissive parenting as much as 36.7%, authoritarian parenting as much as 33.3%, and democratic parenting as much as 30%. The results of observation of 30 children 70% were suspected in language development and 30% of normal in language development. From the results of the chi-square test showed p value of 0.015 is smaller than the value of α is 0.05. There is a relationship between parents' parenting on children's language development.